2007
DOI: 10.1098/rstb.2007.2147
|View full text |Cite
|
Sign up to set email alerts
|

Avian circannual clocks: adaptive significance and possible involvement of energy turnover in their proximate control

Abstract: Endogenous circannual clocks are found in many long-lived organisms, but are best studied in mammal and bird species. Circannual clocks are synchronized with the environment by changes in photoperiod, light intensity and possibly temperature and seasonal rainfall patterns. Annual timing mechanisms are presumed to have important ultimate functions in seasonally regulating reproduction, moult, hibernation, migration, body weight and fat deposition/stores. Birds that live in habitats where environmental cues such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 105 publications
3
80
0
1
Order By: Relevance
“…A possible explanation is that these cycles are residuals of responses that had evolved originally in our ancestors, who-like other tropical species-may have timed physiological processes by circannual clocks and environmental cues. Perhaps we have retained a circannual timer that can be synchronized by photoperiod or metabolic status [15,111,112]. Alternatively, as our ancestors moved from Africa to the higher latitudes and encountered progressively greater variation in food availability and temperature, they could have evolved a strong photoperiodic response [7,24].…”
Section: (B) Urbanizationmentioning
confidence: 99%
“…A possible explanation is that these cycles are residuals of responses that had evolved originally in our ancestors, who-like other tropical species-may have timed physiological processes by circannual clocks and environmental cues. Perhaps we have retained a circannual timer that can be synchronized by photoperiod or metabolic status [15,111,112]. Alternatively, as our ancestors moved from Africa to the higher latitudes and encountered progressively greater variation in food availability and temperature, they could have evolved a strong photoperiodic response [7,24].…”
Section: (B) Urbanizationmentioning
confidence: 99%
“…Early pioneering studies have demonstrated persisting rhythms of annual events in birds kept under constant light conditions for years (Gwinner 1986 understand very little about the physiological and molecular mechanisms that underlie avian circannual rhythmicity (but see Wikelski et al 2008 ). On top of this uncertainty, the regulation of annual cycles has also been quite a mystery, at least until the end of the last century.…”
Section: Light and Circadian Rhythmsmentioning
confidence: 99%
“…There are complex interactions between the reproductive system and the environment that involve state variables other than the state of reproductive system (see Hahn & MacDougall-Shackleton 2008;Paul et al 2008;Wikelski et al 2008). Many studies of behaviour over the annual cycle have shown that cues such as short days trigger a particular phase of the life cycle (e.g.…”
Section: Physiological State Variablesmentioning
confidence: 99%